Development and characterization of an aged onset model of Alzheimer's disease in Drosophila melanogaster. - Mhatre, S.D.; Michelson, S.J.; Gomes, J.; Tabb, L.P.; Saunders, A.J.; Marenda, D.R. (Experimental Neurology, 2014)
The biggest risk factor for developing Alzheimer's disease (AD) is age. Depending on the age of onset, AD is clinically categorized into either the early-onset form (before age 60years old), or the late-onset form (after age 65years old), with the vast majority of AD diagnosed as late onset (LOAD). LOAD is a progressive neurodegenerative disorder that involves the accumulation of ?-amyloid (A?) plaques and neurofibrillary tangles in the brains of elderly patients. Affected individuals often experience symptoms including memory loss, confusion, and behavioral changes. Though many animal models of AD exist, very few are capable of analyzing the effect of older age on AD pathology. In an attempt to better model LOAD, we developed a novel "aged AD" model using Drosophila melanogaster. In our model, we express low levels of the human AD proteins APP (amyloid precursor protein) and BACE1 (?-site APP cleaving enzyme BACE) specifically in the fly's central nervous system. Advantages of our model include the onset of behavioral and neuropathological symptoms later in the fly's lifespan due to a gradual accrual of A? within the central nervous system (CNS), making age the key factor in the behavioral and neuroanatomical phenotypes that we observe in this model.